Hubungan Sumber Daya dan Struktur Birokrasi dengan Implementasi Program UKS dalam Pemeliharaan Kesehatan Gigi Siswa SD Negeri di Kota Medan - Tanjung, Zimahanum; Yustina, Ida; Yanti, Gema Nazri (Universitas Malahayati, 2025)
ABSTRACT The prevalence of dental caries among elementary school students in Medan City has shown a worrying increase over the years. In 2021 and 2022, 4,175 and 19,534 cases were reported, respectively, and the numbers further rose to 46,219 students in 2023. A survey of 30 public elementary schools in the city revealed significant gaps in dental hygiene education and practices, with most schools lacking proper brushing demonstrations, tooth brushing sessions, and regular classroom brushing activities. Additionally, none of the schools received guidance from a dentist, and there was limited coordination with health centers for screenings and check-ups. These findings suggest that the School Health Unit (UKS) program for dental health maintenance in public elementary schools in Medan City is not being optimally implemented. The research problem formulated is the factors affecting the implementation of the UKS program for dental health maintenance in public elementary schools in Medan City. The purpose of this study is to see the relationship between resources and bureaucratic structure and the implementation of UKS in maintaining dental health of State Elementary School students in Medan City. This cross-sectional quantitative study conducted in Medan, Indonesia, from June to July 2024, focuses on the impact of the UKS program on SDN youth health. The research addresses the lack of progress in UKS implementation and the scarcity of research on its impact. Using cluster and simple random sampling techniques, the study involved 382 SDN and 80 SDN respondents. Data was collected through questionnaires and analyzed using a computer system. Univariate and bivariate analyses were employed to understand the impact of the UKS program on SDN youth health and the relationship between health factors and the program's implementation. The study provides insights into the implementation of the UKS program in SDN youth health. A total of 36 elementary schools (45%) have adequate resources, schools that have a good bureaucratic structure are 19 elementary schools (23.8%) and there are 35 elementary schools (43.8%) that have the implementation of the UKS program in maintaining good dental health. There is a relationship between the availability of resources and bureaucratic structure and the implementation of UKS in maintaining dental health of State Elementary School students in Medan City. The variables of resources (p=<0.001) and bureaucratic structure (p=0.001) are related to implementation. Keywords: Implementation, UKS, Dentition, Students ABSTRAK Prevalensi karies gigi di kalangan siswa SD di Kota Medan telah menunjukkan peningkatan yang mengkhawatirkan selama bertahun-tahun. Pada tahun 2021 dan 2022, masing-masing 4.175 dan 19.534 kasus dilaporkan, dan jumlahnya terus meningkat menjadi 46.219 siswa pada tahun 2023. Sebuah survei terhadap 30 sekolah dasar negeri di kota itu mengungkapkan kesenjangan yang signifikan dalam pendidikan dan praktik kebersihan gigi, dengan sebagian besar sekolah tidak memiliki demonstrasi menyikat gigi yang benar, sesi menyikat gigi, dan kegiatan menyikat gigi di kelas secara teratur. Selain itu, tidak ada sekolah yang menerima bimbingan dari dokter gigi, dan ada koordinasi terbatas dengan pusat kesehatan untuk pemeriksaan dan pemeriksaan. Temuan ini menunjukkan bahwa program Unit Kesehatan Sekolah (UKS) untuk pemeliharaan kesehatan gigi di sekolah dasar negeri di Kota Medan belum dilaksanakan secara optimal. Permasalahan penelitian yang dirumuskan adalah faktor-faktor yang mempengaruhi pelaksanaan program UKS untuk pemeliharaan kesehatan gigi di sekolah dasar negeri di Kota Medan. Tujuan penelitian ini adalah untuk melihat hubungan sumber daya dan struktur birokrasi dengan implementasi UKS dalam pemeliharaan kesehatan gigi siswa SD Negeri di Kota Medan. Studi kuantitatif cross-sectional yang dilakukan di Medan, Indonesia, dari Juni hingga Juli 2024 ini, berfokus pada dampak program UKS terhadap kesehatan remaja SDN. Penelitian ini membahas kurangnya kemajuan dalam implementasi UKS dan kelangkaan penelitian tentang dampaknya. Menggunakan teknik cluster dan simple random sampling, penelitian ini melibatkan 382 responden SDN dan 80 SDN. Data dikumpulkan melalui kuesioner dan dianalisis menggunakan sistem komputer. Analisis univariat dan bivariat digunakan untuk memahami dampak program UKS terhadap kesehatan remaja SDN dan hubungan antara faktor kesehatan dan implementasi program. Studi ini memberikan wawasan tentang implementasi program UKS dalam kesehatan siswa SDN. Sebanyak sebanyak 36 SDN (45%) yang memiliki sumber daya yang memadai, sekolah yang memiliki struktur birokrasi yang baik ada sebanyak 19 SDN (23,8%) dan ekolah yang memiliki implementasi program UKS dalam pemeliharaan kesehatan gigi yang baik ada sebanyak 35 SDN (43,8%). Ada hubungan ketersediaan sumber daya dan struktur birokrasi dengan implementasi UKS dalam pemeliharaan kesehatan gigi siswa SD Negeri di Kota Medan. Variabel sumber daya (p=<0,001) dan struktur birokrasi (p=0,001) berhubungan dengan implementasi. Kata Kunci: Implementasi, UKS, Gigi, Siswa